Teams Games Tournament Untuk Meningkatkan Motivasi Belajar Dan Kemampuan Berlatih Lari Pada Siswa Kelas 3 SD Negeri Nganjat Polanharjo Klaten 2018/2019 Semester I - Sri Muryani (Universitas Sebelas Maret, 2019)
The purpose of this study was to find out: (1) Student learning motivation in learning Penjasas with teams games tournament in third grade students of Nganjat Polanharjo Public Elementary School in Klaten Regency 2018/2019; (2) Ability to practice student running in learning Penjasas with team games tournament models for third grade students of Nganjat Polanharjo Elementary School in Klaten Regency 2018/2019. This type of research is Classroom Action Research (CAR), with research procedures: planning, action, observation, and reflection. Data collection techniques use: observation, interviews, and documentation. Based on the results of the study concluded: (1) Team competition game model (TGT) in health facilities can improve student learning motivation during the learning process takes place. Students feel happy, the classroom atmosphere is conducive to learning. Encourage students to learn to cooperate constructively, cooperate with each other, and avoid selfishness that tends to stand out; (2) Team competition game model (TGT) in health facilities can improve students' ability to practice running. Students try to use their abilities to win the race. Learning resources are not focused solely on the teacher, but are obtained from interactions between existing students.